A method for homogenizing positive electrode slurry
By mixing the conductive agent with the glue solution to make the conductive adhesive solution and mixing it with the positive electrode material in four steps, the problem of reducing the proportion of conductive agent auxiliary materials and the positive electrode main material in the prior art is solved, and the power of the battery cell is significantly improved Performance and cycling performance.
Patent Information
- Application Number
- CN202211146111.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-20
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-09-20
AI Technical Summary
When the existing lithium-ion battery positive electrode homogenization method improves slurry uniformity and fluidity, the ratio of conductive agent auxiliary materials and positive electrode main materials is reduced, thereby reducing the power performance of the battery cell.
Pre-mix the conductive agent and the glue solution to make the conductive adhesive solution, and mix the conductive adhesive solution with the positive electrode material in four steps, adjust the ratio of the conductive agent and the glue solution and the ratio gradually added to the positive electrode material to improve the positive electrode material and the conductivity. ratio of agent.
Through this method, the power and cycle performance of the battery cell are significantly improved, the discharge power of 50% SOC 10s is increased by 30%, and the number of cycles is increased by 50%.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a homogenizing method for positive electrode slurry. Background Art
[0002] The lithium-ion positive electrode slurry process is the most important step in the lithium-ion manufacturing process. For high-power and long-cycle batteries, the uniform dispersion of the positive electrode slurry is particularly important.
[0003] CN114156431A discloses a positive electrode homogenization method, a positive electrode slurry and its application, the positive electrode homogenization method comprises the following steps: 1) mixing a conductive agent auxiliary material, a first binder and a positive electrode active material into a mass; 2) mixing a PVP dispersion liquid and the mass to obtain a first dispersion; 3) using the first dispersion, a conductive agent main material and a second binder to homogenize the slurry to obtain a positive electrode slurry; the first binder comprises at least one of polyimide and modified polyimide. The conductive agent auxiliary material, the first binder and the positive electrode active material are mixed into a mass, the PVP dispersion liquid is mixed with the mass to obtain the first dispersion, and the first dispersion conductive agent main material and the second binder are further homogenized to obtain a slurry. The system improves the fluidity of the slurry by adding a dispersion liquid, adding two binders and a positive electrode material in two steps, but the addition of the dispersion liquid and the two binders reduces the ratio of the conductive agent auxiliary material to the positive electrode main material, and reduces the power performance of the battery cell.
[0004] CN103022420A discloses a lithium-ion power battery positive electrode homogenization method for improving the uniformity of electrode slurry, comprising the following steps: placing a dry powder conductive agent and a diluted binder in a homogenizer with a circulating water cooling function and stirring at a low speed of 20 rpm and a high speed of 2000 rpm for 30 minutes; adding a paste conductive agent and N-methyl pyrrolidone, stirring at a low speed of 20 rpm and a high speed of 2000 rpm for 60 minutes; adding an active material material and stirring at a low speed of 20 rpm for 10 minutes, and then stirring at a low speed of 20 rpm and a high speed of 2000 rpm for 60 minutes. The dry powder conductive agent and the diluted binder are directly placed in a homogenizer with a circulating water cooling function for stirring, and finally N-methyl pyrrolidone is added for dilution. Although the production process is simplified and the production efficiency is improved, when the proportion of the positive electrode material and the conductive agent in the slurry is high, the slurry is difficult to disperse during the stirring process, and the operating power requirements of the equipment are high. Summary of the invention
[0005] The object of the present invention is to provide a method for homogenizing positive electrode slurry. The present invention pre-mixes a conductive agent and a glue to form a conductive glue, and then mixes the conductive glue and the positive electrode material in four steps, which can not only improve the uniformity and fluidity of the slurry, but also avoid high wear on the homogenization equipment.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for homogenizing a positive electrode slurry, the homogenizing method comprising the following steps:
[0008] (1) dividing the conductive agent into two parts, mixing one part of the conductive agent with the glue to obtain a conductive glue, dividing the conductive glue into four parts, dry-mixing the remaining part of the conductive agent with the positive electrode material, and then adding the first part of the conductive glue to perform one-step mixing to obtain a one-step slurry;
[0009] (2) mixing the first-step slurry with the second part of the conductive adhesive in two steps to obtain a two-step slurry;
[0010] (3) mixing the second-step slurry with the third part of the conductive adhesive in three steps to obtain a three-step slurry;
[0011] (4) mixing the third-step slurry with the fourth part of the conductive glue in four steps to obtain a positive electrode slurry;
[0012] Wherein, taking the mass of the conductive adhesive in step (1) as 100%, the mass fraction of the conductive agent is 2.5-3.5%, for example: 2.5%, 2.8%, 3%, 3.2% or 3.5%.
[0013] The present invention mixes the conductive agent with the glue solution and then with the positive electrode material, thereby avoiding the loss of equipment caused by the direct mixing of the three. By adjusting the ratio of the conductive agent to the glue solution and the ratio gradually added to the positive electrode material, the ratio of the positive electrode material and the conductive agent in the system composed of the positive electrode material, the conductive agent and the glue solution can be increased to a higher ratio, thereby improving the power performance and cycle performance of the battery cell.
[0014] The slurry obtained by the homogenization method of the present invention can produce a battery cell with a 50% SOC 10s discharge power of up to 1050W, which is 30% higher than the power of the slurry obtained by the traditional homogenization method, and the number of cycles can reach 15,000 cycles, which is 50% higher than the cycle performance of the slurry obtained by the traditional homogenization method.
[0015] Preferably, the conductive agent in step (1) comprises conductive carbon black.
[0016] Preferably, the density of the conductive agent in step (1) is 80 to 130 kg / m 3 , for example: 80kg / m 3 , 90kg / m 3 , 100kg / m 3 、110kg / m 3 , 120kg / m 3 or 130kg / m 3 wait.
[0017] Preferably, the specific surface area of the conductive agent in step (1) is 30 to 80 g / m 3 , for example: 30g / m 3 , 40g / m 3 , 50g / m 3 , 60g / m 3 , 70g / m 3 or 80g / m 3 wait.
[0018] Preferably, the glue solution includes polyvinylidene fluoride solution.
[0019] Preferably, the positive electrode material comprises a ternary positive electrode material.
[0020] Preferably, the ternary positive electrode material includes any one of NCM811, NCM622, NCM532 or NCM333, or a combination of at least two of them.
[0021] Preferably, the mass fraction of the positive electrode material in the slurry in step (1) is 86-90%, for example: 86%, 87%, 88%, 89% or 90%.
[0022] Preferably, the mass fraction of the positive electrode material in the second-step slurry in step (2) is 76-80%, for example: 76%, 77%, 78%, 79% or 80%.
[0023] Preferably, the mass fraction of the positive electrode material in the three-step slurry in step (3) is 70-73%, for example: 70%, 71%, 72% or 73%, etc.
[0024] Preferably, the mass fraction of the positive electrode material in the four-step slurry in step (4) is 63-67%, for example: 63%, 64%, 65%, 66% or 67%.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention can increase the ratio of positive electrode material to conductive agent in the system consisting of positive electrode material, conductive agent and glue solution to a higher ratio by adjusting the ratio of conductive agent to glue solution and gradually adding the ratio to positive electrode material, thereby improving the power performance and cycle performance of the battery cell.
[0027] (2) The 24-hour viscosity change rate of the slurry obtained by the homogenization method of the present invention can reach less than 185%, and the difference in solid content between the upper and lower layers can reach less than 0.20% within 24 hours, showing good stability. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0029] The mass ratios of the positive electrode material mass, the total mass of the conductive agent and the polyvinylidene fluoride in the examples of the present invention and the comparative examples are all 95:2:3.
[0030] Example 1
[0031] This embodiment provides a method for homogenizing a positive electrode slurry, and the homogenizing method comprises the following steps:
[0032] (1) The density is 100 kg / m 3 , specific surface area is 50g / m 3 The conductive carbon black is divided into two parts, one part of the conductive carbon black is mixed with an N-methylpyrrolidone (NMP) solution of polyvinylidene fluoride to obtain a conductive glue having a mass fraction of 3% of the conductive carbon black, the conductive glue is divided into four parts, the remaining part of the conductive carbon black is dry-mixed with the NCM811 positive electrode material, and then added to the first part of the conductive glue for one-step mixing to obtain a one-step slurry, wherein the mass fraction of the NCM811 positive electrode material in the one-step slurry is 88%;
[0033] (2) mixing the first-step slurry with the second part of the conductive adhesive in two steps to obtain a second-step slurry, wherein the mass fraction of the NCM811 positive electrode material in the second-step slurry is 77%;
[0034] (3) mixing the second-step slurry with the third part of the conductive glue in three steps to obtain a three-step slurry, wherein the mass fraction of the NCM811 positive electrode material in the three-step slurry is 72%;
[0035] (4) The third-step slurry and the fourth part of the conductive adhesive are mixed in four steps to obtain a positive electrode slurry, wherein the mass fraction of the NCM811 positive electrode material in the positive electrode slurry is 66%.
[0036] Example 2
[0037] This embodiment provides a method for homogenizing a positive electrode slurry, and the homogenizing method comprises the following steps:
[0038] (1) The density is 110kg / m 3 , specific surface area is 60g / m 3The conductive carbon black is divided into two parts, one part of the conductive carbon black is mixed with the NMP solution of polyvinylidene fluoride to obtain a conductive glue with a mass fraction of 3.1% of the conductive carbon black, the conductive glue is divided into four parts, the remaining part of the conductive carbon black is dry-mixed with the NCM811 positive electrode material, and then added to the first part of the conductive glue for one-step mixing to obtain a one-step slurry, wherein the mass fraction of the NCM811 positive electrode material in the one-step slurry is 87%;
[0039] (2) mixing the first-step slurry with the second part of the conductive adhesive in two steps to obtain a second-step slurry, wherein the mass fraction of the NCM811 positive electrode material in the second-step slurry is 78%;
[0040] (3) mixing the second-step slurry with the third part of the conductive glue in three steps to obtain a three-step slurry, wherein the mass fraction of the NCM811 positive electrode material in the three-step slurry is 71%;
[0041] (4) The third-step slurry and the fourth part of the conductive adhesive are mixed in four steps to obtain a positive electrode slurry, wherein the mass fraction of the NCM811 positive electrode material in the positive electrode slurry is 64%.
[0042] Example 3
[0043] This embodiment provides a method for homogenizing a positive electrode slurry, and the homogenizing method comprises the following steps:
[0044] (1) Dividing carbon nanotubes into two parts as conductive agents, mixing one part of the carbon nanotubes with an NMP solution of polyvinylidene fluoride to obtain a conductive adhesive solution with a mass fraction of 3% of carbon nanotubes, dividing the conductive adhesive solution into four parts, dry-mixing the remaining part of the carbon nanotubes with NCM811 positive electrode materials, and then adding the first part of the conductive adhesive solution to perform one-step mixing to obtain a one-step slurry, wherein the mass fraction of the NCM811 positive electrode material in the one-step slurry is 88%;
[0045] (2) mixing the first-step slurry with the second part of the conductive adhesive in two steps to obtain a second-step slurry, wherein the mass fraction of the NCM811 positive electrode material in the second-step slurry is 77%;
[0046] (3) mixing the second-step slurry with the third part of the conductive glue in three steps to obtain a three-step slurry, wherein the mass fraction of the NCM811 positive electrode material in the three-step slurry is 72%;
[0047] (4) The third-step slurry and the fourth part of the conductive adhesive are mixed in four steps to obtain a positive electrode slurry, wherein the mass fraction of the NCM811 positive electrode material in the positive electrode slurry is 66%.
[0048] Example 4
[0049] The only difference between this embodiment and embodiment 1 is that the mass fraction of the positive electrode material in the one-step slurry is 80%, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0050] Example 5
[0051] The only difference between this embodiment and embodiment 1 is that the mass fraction of the positive electrode material in the one-step slurry is 93%, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0052] Example 6
[0053] The only difference between this embodiment and embodiment 1 is that the mass fraction of the positive electrode material in the second-step slurry is 70%, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0054] Example 7
[0055] The only difference between this embodiment and embodiment 1 is that the mass fraction of the positive electrode material in the second-step slurry is 85%, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0056] Example 8
[0057] The only difference between this embodiment and embodiment 1 is that the mass fraction of the positive electrode material in the three-step slurry is 65%, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0058] Example 9
[0059] The only difference between this embodiment and embodiment 1 is that the mass fraction of the positive electrode material in the three-step slurry is 75%, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0060] Example 10
[0061] The only difference between this embodiment and embodiment 1 is that the mass fraction of the positive electrode material in the positive electrode slurry is 60%, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0062] Embodiment 11
[0063] The only difference between this embodiment and embodiment 1 is that the mass fraction of the positive electrode material in the positive electrode slurry is 70%, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0064] Comparative Example 1
[0065] The only difference between this comparative example and Example 1 is that the mass fraction of the conductive carbon black in the conductive adhesive is 2%, and the other conditions and parameters are exactly the same as those in Example 1.
[0066] Comparative Example 2
[0067] The only difference between this comparative example and Example 1 is that the mass fraction of the conductive carbon black in the conductive glue is 4%, and the other conditions and parameters are exactly the same as those in Example 1.
[0068] Comparative Example 3
[0069] The only difference between this comparative example and Example 1 is that the conductive glue is directly mixed with the positive electrode material in one step, and the other conditions and parameters are exactly the same as those in Example 1.
[0070] Performance Test:
[0071] The positive electrode slurry obtained in Examples 1-11 and Comparative Examples 1-3 was tested for stability performance. A cup of slurry was taken and left to stand for 24 hours. After 24 hours, the slurry on the upper and bottom layers of the cup was taken for solid content testing. The difference in solid content between the upper and lower layers can reflect the slurry sedimentation performance, i.e., stability performance. The positive electrode slurry was coated on the surface of aluminum foil and dried to form a positive electrode sheet. The negative electrode active material, negative electrode binder, negative electrode stabilizer, and negative electrode conductive agent were added to distilled water and mixed evenly to prepare a negative electrode slurry. The negative electrode slurry was then evenly coated on copper foil. After drying, it was rolled and cut in sequence to obtain a negative electrode sheet; wherein the weight ratio of the negative electrode active material, the negative electrode binder, the negative electrode stabilizer, and the negative electrode conductive agent was 95:2:1.5:1.5. The positive electrode sheet is used as the positive electrode, and the negative electrode sheet is used as the negative electrode to assemble into a liquid lithium ion battery and a hybrid solid-liquid lithium ion battery. The liquid lithium ion battery and the hybrid solid-liquid lithium ion battery are subjected to charge and discharge tests, rate performance, and cycle performance. The test results are shown in Table 1:
[0072] Table 1
[0073] 24h viscosity change (%) 24h difference in solid content between upper and lower layers (%) Example 1 180 0.15 Example 2 185 0.20 Example 3 196 0.25 Example 4 190 0.24 Example 5 188 0.35 Example 6 189 0.32 Example 7 196 0.35 Example 8 188 0.30 Example 9 190 0.32 Example 10 195 0.28 Embodiment 11 193 0.32 Comparative Example 1 190 0.22 Comparative Example 2 210 0.23 Comparative Example 3 350 1.56
[0074] As can be seen from Table 1, from Examples 1-2, the 24h viscosity change rate of the slurry prepared by the homogenization method of the present invention can reach less than 185%, and the 24h difference in solid content between the upper and lower layers can reach less than 0.20%, showing good stability.
[0075] By comparing Example 1 and Example 3, it can be seen that the homogenization method of the present invention uses conductive carbon black as a conductive agent, and the conductive carbon black has a small particle size, a large specific surface area, and excellent power performance.
[0076] By comparing Example 1 with Examples 4-11, it can be seen that the homogenization process of the present invention is divided into four times to mix the conductive glue with the mixture of the positive electrode main material and part of the conductive agent, wherein the mass fraction of the positive electrode material in the slurry obtained in each step will affect the homogenization effect. The mass fraction of the positive electrode material in the first-step slurry is controlled at 86-90%, the mass fraction of the positive electrode material in the second-step slurry is controlled at 76-80%, and the mass fraction of the positive electrode material in the three-step slurry is controlled at 70-73%. The mass fraction of the positive electrode material in the positive electrode slurry is controlled at 63-67%, and the homogenization effect is better. If it exceeds this range, the slurry fluidity is poor and coating is difficult.
[0077] By comparing Example 1 and Comparative Examples 1-2, it can be seen that during the homogenization process of the present invention, the mass fraction of the conductive agent in the conductive adhesive will affect the homogenization effect. When the mass fraction of the conductive agent in the conductive adhesive is controlled at 2.5-3.5%, the homogenization effect is better. If the mass fraction of the conductive agent is too low, the power performance is poor. If the mass fraction of the conductive agent is too high, the slurry fluidity is poor and homogenization coating is difficult.
[0078] By comparing Example 1 and Comparative Example 3, it can be seen that the present invention can increase the ratio of positive electrode material and conductive agent in the system consisting of positive electrode material, conductive agent and glue to a higher ratio by adjusting the ratio of conductive agent to glue and the ratio of gradually added to the positive electrode material, thereby improving the power performance and cycle performance of the battery cell.
[0079] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for homogenizing a positive electrode slurry, characterized in that: The homogenization method comprises the following steps: (1) dividing the conductive agent into two parts, mixing one part of the conductive agent with the glue to obtain a conductive glue, dividing the conductive glue into four parts, dry-mixing the remaining part of the conductive agent with the positive electrode material, and adding the first part of the conductive glue to perform one-step mixing to obtain a one-step slurry, wherein the mass fraction of the positive electrode material in the one-step slurry is 86-90%; (2) mixing the first-step slurry with the second part of the conductive adhesive in two steps to obtain a second-step slurry, wherein the mass fraction of the positive electrode material in the second-step slurry is 76-80%; (3) mixing the second-step slurry with the third part of the conductive adhesive in three steps to obtain a three-step slurry, wherein the mass fraction of the positive electrode material in the three-step slurry is 70-73%; (4) mixing the third-step slurry with the fourth part of the conductive glue in four steps to obtain a positive electrode slurry, wherein the mass fraction of the positive electrode material in the positive electrode slurry is 63-67%; Wherein, based on the mass of the conductive adhesive in step (1) being 100%, the mass fraction of the conductive agent is 2.5-3.5%, and the conductive agent includes conductive carbon black.
2. The homogenization method according to claim 1, characterized in that The density of the conductive agent in step (1) is 80-130 kg / m 3 .
3. The homogenization method according to claim 1, characterized in that The specific surface area of the conductive agent in step (1) is 30 to 80 g / m 3 .
4. The homogenization method according to claim 1, characterized in that The glue solution includes polyvinylidene fluoride solution.
5. The homogenization method according to claim 1, characterized in that The positive electrode material in step (1) includes a ternary positive electrode material.
6. The homogenization method according to claim 5, characterized in that The ternary positive electrode material includes any one of NCM811, NCM622, NCM532 or NCM333, or a combination of at least two of them.
Citation Information
Patent Citations
Slurry homogenizing method for positive electrode of lithium-ion power battery
CN103022420A
Lithium-sulfur battery
CN105702944A
A lithium battery positive electrode slurry and proces technology thereof
CN109167068A